PENGATURAN MASA JABATAN KEPALA DAERAH DALAM HUKUM POSITIF INDONESIA - Puji Rahayu, Nunung; Widya Kartika, Adhitya (Kertha Semaya : Journal Ilmu Hukum, 2023)
Penelitian ini dilakukan untuk mengetahui dan mengidentifikasi konflik norma pengaturan masa jabatan Kepala Daerah dalam hukum positif di Indonesia khususnya masa jabatan Kepala Daerah hasil Pemilihan Kepala Daerah tahun 2020 yang dihubungkan dengan teori harmonisasi hukum. Penelitian ini menggunakan metode yuridis normatif statue approach. Hasil dari penelitian ini menyatakan bahwa hakim dalam menilai bertentangan atau tidak suatu undang-undang dengan UUD NRI 1945 sangat bergantung pada penafsiran mana yang digunakan dan ketidakselarasan antara norma yang mengatur tentang masa jabatan Kepala Daerah dapat dilakukan menggunakan harmonisasi vertikal dengan asas lex superiori derogate legi inferiori. This research was conducted to determine and identify the conflict of norms regulating of the term of office of the Regional Head in positive law in Indonesia, especially the term of office of the Regional Head as a result of the 2020 Regional Head Election which is related to the theory of legal harmonization. This study adopts a normative juridical approcah while talking a legislative perspevtive. The results of this research demonstrate that judges' evaluations of regulations that either contradict or are not in contradiction to the 1945 Constitution depend on the interpretation that is implemented, and that vertical harmonization in line with the lex superiori derogate legi inferiori principle can be utilized to fix contradictions between the regulations governing the Regional Head’s term of office.